Cost savings with hemin versus givosiran for the treatment of patients with acute intermittent porphyria (AIP). (1st December 2020) - Massachi, Samira; Epstein, Josh; Hurd, Julie; Bonkovsky, Herbert L.
Abstract: Objective: Since 1983, hemin has been FDA-approved for acute intermittent porphyria (AIP) attacks. In 2019, FDA approved givosiran for the treatment of adults with acute hepatic porphyria. The objective of this research was to estimate and compare the total cost of AIP-related healthcare for patients treated with hemin or givosiran. Methods: A microsimulation cost model was developed to estimate the annual economic impact of hemin versus givosiran treatment for patients with AIP from the U.S. healthcare payer perspective. Hemin treatment costs were calculated from the Hemin Shipment Data in which patients were defined as receiving acute attack treatment or prophylaxis treatment based on shipment patterns. Three separate hemin subpopulations were considered: one attack per year, multiple attacks per year, and hemin prophylaxis. Treatment costs for givosiran (with hemin for acute attacks) were simulated based on Phase III trial efficacy results applied to individual treatment histories in the Hemin Shipment Data. Other healthcare utilization was also considered. Outcomes were annualized and expenditures inflated to 2019. Results: For all patients with AIP, the average annual total cost of care with hemin was 78% lower (difference = $482, 113; 95% CI=$373, 638–$594, 778) than the average annual total cost of care with givosiran. Average annual total cost of care with hemin was between 46% and 92% lower than givosiran for the three hemin subpopulations: one attack per year (difference = $545, 219; 95% CI=$436, 584–$657, 239), multiple attacks per year (difference = $459, 366; 95% CI=$350, 291–$574, 403), and hemin prophylaxis (difference = $311, 950; 95% CI=$191, 898–$435, 893). Cost savings with hemin were robust to one-way and probabilistic sensitivity as well as scenario analyses. Conclusions: Hemin is expected to provide cost savings compared to givosiran for all AIP patients and subpopulations. Lower annual total costs of care with hemin range from $311, 950 to $545, 219 less depending on whether the patient uses hemin prophylactically or for acute treatment attacks.